2011
DOI: 10.1007/978-94-007-2027-5_7
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale Modelling of the Arctic Atmospheric Boundary Layer and Its Interaction with Sea Ice

Abstract: This chapter summarises mesoscale modelling studies, which were carried out during the ACSYS decade until 2005. They were aiming at the parameterisation and improved understanding of processes in the Arctic boundary layer over the open ocean and marginal sea ice zones and over the Greenland ice sheet. It is shown that progress has been achieved with the parameterization of fluxes in strong convective situations such as cold-air outbreaks and convection over leads. A first step was made towards the parameteriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 93 publications
0
17
0
Order By: Relevance
“…Dare and Atkinson, ). A comprehensive summary of previous studies on lead–atmosphere interactions can be found in Vihma et al () and Lüupkes et al (, ), but some findings will be summarized in the following to demonstrate the relevance of the present study.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Dare and Atkinson, ). A comprehensive summary of previous studies on lead–atmosphere interactions can be found in Vihma et al () and Lüupkes et al (, ), but some findings will be summarized in the following to demonstrate the relevance of the present study.…”
Section: Introductionmentioning
confidence: 76%
“…Measurements of the surface energy budget over a large sea‐ice‐covered region could be most effective when the flight patterns could be restricted to long transect flights directed straight ahead and crossing a large number of different leads (as performed by Brümmer and Thiemann, ; Lüpkes et al , ). However, this is only possible when an arbitrary orientation of a flight track relative to the orientation of a lead is sufficient for the determination of fluxes.…”
Section: Calculation Of Turbulent Fluxes For Horizontal Flight Legsmentioning
confidence: 99%
See 1 more Smart Citation
“…The parametrization of the MIZ surface roughness has been discussed intensively during the last three decades, starting with studies by Overland [1985] and Guest and Davidson [1987]. A general finding of Andreas et al [1984], Hanssen‐Bauer and Gjessing [1988], Stössel and Claussen [1993], Mai et al [1996], Birnbaum and Lüpkes [2002], Lüpkes and Birnbaum [2005], and Lüpkes et al [2012] was that atmospheric momentum fluxes are influenced not only by the skin drag of the open water surface and of the more or less plane ice floe surfaces but also by the form drag caused by the edges of floes, where often small ridges form due to floe collisions. So, the effective atmospheric drag over the MIZ was parametrized by accounting for both skin drag and form drag using schemes of different complexity.…”
Section: Introductionmentioning
confidence: 99%
“…In the first approach it is set to a constant value. Two different values are applied that are typical for the Arctic BL (Lüpkes et al, 2012b). The first one, 350 m, was, for example, measured over a flaw lead polynya in the Canadian Archipelago by Raddatz et al (2011).…”
Section: Box Modelmentioning
confidence: 99%